The Role of Supply Chain Management Practices in Mediating the Effect of Knowledge Management on Company Performance: A Study on Laptop Shops in Ambon City - Zainuddin Latuconsina; Agnes Soukotta; Sulasri Kaisupy; Pandu Adi Cakranegara; Muhammad Hery Santoso (Quantitative Economics and Management Studies, 2022)
The purpose of this study was to analyze the effect of knowledge management on company performance through supply chain management practices in laptop shops in Ambon city. The population in this study were 33 owners/employees at a laptop shop in Ambon city. The analytical technique used in this research is Partial Least Square (PLS). The results showed that knowledge management has a positive effect on company performance, knowledge management has a positive influence on supply chain management practices and supply chain management practices have a positive effect on company performance.